Promoting income tax compliance among the self-employed in the tamale metropolis of Ghana - Naporow, Issah Yakubu (2016)
A thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of Masters of Business Administration (Accounting Option),